(untitled) (International Conference on Energy, Intelligence Systems, and Cloud Computing (Ingenio 2026), 2026)
To address the grid-connected current distortion caused by back ground grid harmonics in virtual synchronous generator (VSG)-controlled PV storage systems, an adaptive virtual harmonic impedance-based harmonic sup pression strategy is proposed. First, an equivalent impedance model of the VSG grid-connected system is established to analyze the influence of background harmonics on the grid-connected current. Then, a hybrid generalized integrator composed of cascaded TOGI and SOGI is employed to extract the fundamental and harmonic currents, based on which the virtual harmonic impedance is constructed. Furthermore, an adaptive virtual impedance control method is designed according to the harmonic content variation of the grid-connected current to realize online adjustment of the virtual inductance. Simulation results demonstrate that the proposed method can effectively reduce the harmonic content of the grid connected current, improve power quality, and provide satisfactory dynamic performance.